2020 IEEE 91st Vehicular Technology Conference (VTC2020-Spring) 2020
DOI: 10.1109/vtc2020-spring48590.2020.9128625
|View full text |Cite
|
Sign up to set email alerts
|

An Initial Access Optimization Algorithm for millimeter Wave 5G NR Networks

Abstract: The millimeter wave (mmWave) communication uses directional antennas. Hence, achieving fine alignment of transmit and receive beams at the initial access phase is quite challenging and time-consuming. In this paper, we provide a dynamic-weight based beam sweeping direction and synchronization signal block (SSB) allocation algorithm to optimize the cell search of the initial access in mmWave 5G NR networks. The number of SSBs transmitted in each beam sweeping direction depends on previously learned experience w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The availability of cell context information at the BS was shown to reduce the search delay of analog beamforming in [9]. A heuristic weight-based beam sweeping algorithm to improve the cell search in mmWave 5G networks is given in [10]. In [11], an initial access scheme is developed with the aim to minimize the initial access delay by optimizing the activated beams and regions at each slot.…”
Section: Introductionmentioning
confidence: 99%
“…The availability of cell context information at the BS was shown to reduce the search delay of analog beamforming in [9]. A heuristic weight-based beam sweeping algorithm to improve the cell search in mmWave 5G networks is given in [10]. In [11], an initial access scheme is developed with the aim to minimize the initial access delay by optimizing the activated beams and regions at each slot.…”
Section: Introductionmentioning
confidence: 99%
“…Given the importance of this procedure, optimization of BM performance has been extensively pursued in the literature. In [3], a dynamic weight-based algorithm is proposed for initial access (IA) synchronization signal block (SSB) allocation, using static user distribution, to optimize the number of SSBs per sweeping direction. The authors in [4] introduce different beam switching algorithms to improve robustness of BM operations for intra-cell mobility scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…Authors in [7] discuss and compared IA approaches suggested for 5G networks such as iterative, and exhaustive search. The authors of [8] propose an algorithm that dynamically scales the resources allocated to beam sweeping directions to optimize the beam management of the IA procedure in 5G mmWave networks. Recently, machine learning (ML) based approaches have been explored as alternatives to replace conventionally non-ML bases systems in communication systems [9]- [11].…”
Section: Introductionmentioning
confidence: 99%